Respuesta :

The answer is:  45 * 10 ⁻¹¹ .
___________________________________________

Explanation:
____________________________________________
Given:   (9 * 10⁻⁵) * (5 *10 ⁻⁶) ;   Simplify.
____________________________________________
 (9 * 10⁻⁵) * (5 *10⁻⁶)  =

9 * 5 * 10⁻⁵ * 10⁻⁶ = 

(9 * 5) * 10⁻⁵ * 10⁻⁶ 

45 * 10⁻⁵ * 10⁻⁶  ;   
______________________________________
Note the following property of exponents:

xᵃ * xᵇ = x⁽ᵃ⁺ᵇ⁾ ;

As such, 10⁻⁵ * 10⁻⁶ = 10⁽⁻⁵ ⁺ ⁻⁶) = 10 ⁻¹¹ ;
______________________________________
So;  45 * 10⁻⁵ * 10⁻⁶ 

           =  45 * 10⁻¹¹ .
______________________________________